Endoscopic appearances of polypoid type 1 gastric microcarcinoids by narrow-band imaging: a case series in a referral center. Issue 4 (April 2016) - Lahner, Edith; Esposito, Gianluca; Angeletti, Stefano; Corleto, Vito D.; Pilozzi, Emanuela; Di Giulio, Emilio; Annibale, Bruno
Abstract : Objective: Narrow-band imaging (NBI) has been associated with high accuracy for the identification of gastric malignant lesions. This study aimed to investigate for the first time the endoscopic NBI appearances of type 1 gastric carcinoids in a consecutive series of patients with atrophic gastritis. Methods: Seven consecutive patients (five women, median age 61 years) with atrophic gastritis and polypoid type 1 gastric carcinoids were included. After white-light examination, gastric antrum and body were examined by NBI for the examination of polyps and lesions. Digital images of polyps from recorded videos were extracted and reviewed for NBI features. Results: Fifteen polypoid type 1 gastric microcarcinoids (median size 3 mm) were detected in the seven patients; four patients had synchronous lesions. Nine (60%) lesions showed a tubulovillous and six lesions (40%) showed an irregular mucosal pattern; a regular circular pattern was never observed. A light-blue crest was observed on six (40%) lesions. The vascular pattern was irregular in eight (53.3%) microcarcinoids. All six type 1 gastric carcinoids with an irregular mucosal pattern showed an irregular vascular pattern without light-blue crest. Of the nine carcinoids with a tubulovillous mucosal pattern, two had an irregular and seven had a regular vascular pattern. Conclusion: Polypoid type 1 gastric microcarcinoids always show an abnormal NBI mucosal surface pattern, but no specific features to distinguish them from other intraepithelial lesions such as intestinal metaplasia, adenomas, or low-grade and high-grade dysplasia are observed. Thus, target biopsies to diagnose the pathological nature of the lesion are advocated.